2006
DOI: 10.1200/jco.2005.03.6491
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Study Comparing Oral Topotecan to Intravenous Docetaxel in Patients With Pretreated Advanced Non–Small-Cell Lung Cancer

Abstract: Oral topotecan provides activity in the treatment of relapsed, locally advanced, unresectable NSCLC. Both regimens were well tolerated with differing safety profiles. Topotecan may provide an option for patients who desire an orally available treatment after relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 9 publications
3
53
1
1
Order By: Relevance
“…A randomized phase III trial in 829 patients found that oral topotecan was not inferior to docetaxel. 287 If disease progression occurs after second-or third-line chemotherapy, patients with a PS of 0 to 2 may be treated with best supportive care or be enrolled in a clinical trial. Best supportive care only should be provided to patients with a PS of 3 to 4 and progressive disease during any stage of the treatment (see NCCN Clinical Practice Guidelines in Oncology [NCCN Guidelines] on Palliative Care; to view the most recent version of these guidelines, visit the NCCN Web site at www.NCCN.org).…”
Section: Treatment Of Recurrences and Distant Metastasesmentioning
confidence: 99%
“…A randomized phase III trial in 829 patients found that oral topotecan was not inferior to docetaxel. 287 If disease progression occurs after second-or third-line chemotherapy, patients with a PS of 0 to 2 may be treated with best supportive care or be enrolled in a clinical trial. Best supportive care only should be provided to patients with a PS of 3 to 4 and progressive disease during any stage of the treatment (see NCCN Clinical Practice Guidelines in Oncology [NCCN Guidelines] on Palliative Care; to view the most recent version of these guidelines, visit the NCCN Web site at www.NCCN.org).…”
Section: Treatment Of Recurrences and Distant Metastasesmentioning
confidence: 99%
“…Docetaxel demonstrated similar activity in squamous and non-squamous patients. While not approved for second-line therapy in Canada, topotecan, vinflunine, and gefitinib have also demonstrated outcomes similar to those with docetaxel in randomized trials [50][51][52] .…”
Section: Second-and Third-line Therapy In Advanced Nsclcmentioning
confidence: 99%
“…Eight trials of firstline chemotherapy (23-29) and 5 trials of second-line The FDA analyzed by the 50% effect retention method independently (11 (7,(30)(31)(32)(33) were published in advanced non-small cell lung cancer (NSCLC; Table 3). Active controls were platinum-doublet regimens in all the trials of firstline chemotherapy and were docetaxel in all the trials of second-line chemotherapy.…”
Section: Review In Selected Cancersmentioning
confidence: 99%